Contributions of physical education to mental health care in Primary Health Care (Research, Society and Development, 2023)
The research aimed to investigate and discuss the contribution of physical education to mental health care in Primary Care based on the perception of professionals linked to the Expanded Family Health Center in municipalities of Baixada Santista in the state of São Paulo. It is an exploratory research, case study with a qualitative approach. and content analysis through semi-structured interviews through the Google Meet platform. As a result, it was observed that it is through sport, physical exercise, physical activity, the promotion of body culture, community experiences and experiences of relationships that the perceptions of mental health care in the practice of education professionals seek alternatives to contribute to mental health care in Primary Care. In conclusion, the contributions of physical education to mental health care in primary care, despite being based on a logic of care based on the illness, it is noted the effort of professionals to promote well-being through specific tools, the dialogue with other professionals from its nucleus and the health network.